2019
DOI: 10.1111/bjet.12758
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of intelligent tutoring systems on K‐12 students' reading comprehension: A meta‐analysis

Abstract: This meta‐analysis examined the effectiveness of improving reading comprehension for students in K‐12 classrooms using intelligent tutoring systems (ITSs), a computer‐based learning environment that provides customizable and immediate feedback to the learner. Nineteen studies from 13 publications incorporating approximately 10 000 students were included in the final analysis; using robust variance estimation to account for statistical dependencies, the 19 studies yielded 88 effect size estimates. The meta‐anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…For the case when strings are of different lengths there is a question, which one of the two numbers of the word forms should be stated in the formula (2). It is obvious, if we compare the number of matches with the smaller of two values the similarity rate could be higher.…”
Section: The Sql-queries Parsing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case when strings are of different lengths there is a question, which one of the two numbers of the word forms should be stated in the formula (2). It is obvious, if we compare the number of matches with the smaller of two values the similarity rate could be higher.…”
Section: The Sql-queries Parsing Methodsmentioning
confidence: 99%
“…In the recent decades information technology (IT) significantly transformed the environment of human life. They are currently used as a main tool for the information and knowledge processing [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the study was conducted on the effectiveness of intelligent tutoring systems on K-12 students' reading comprehension, based on the result of the study ITSs produce a larger effect size on reading comprehension when compared to traditional instruction, ITSs for reading produce a small effect size when compared to human tutoring. The effect size of ITSs on reading comprehension is inflated when studies use researcher-designed tests [16]. These results may be of interest to researchers and policymakers aiming to enhance reading comprehension through the use of reliable and widely available ITSs.…”
Section: Intelligent Tutoring Systemmentioning
confidence: 98%
“…However, this study found that ITSs yield a larger effect size than the standard teaching process. [6] Additionally, an Intelligent Tutoring System aims to provide immediate and customized instruction or feedback to learners, usually without requiring intervention from a human teacher. According to Ken Koedinger, professor of human-computer interaction and psychology, Intelligent Tutoring Systems are programmed to monitor student success in real-time, include next-step hints, and select practice tasks that help students develop new skills.…”
Section: Introductionmentioning
confidence: 99%
“…For much of the last 30 years, the AI in education community has been focusing on creating AI-based systems, such as Intelligent Tutoring Systems (ITSs), Intelligent Learning Environments (ILEs) and AI-driven educational robots (Serholt et al, 2017;Roll & Wylie, 2016;Nye, 2015), to mimic expert human one-to-one tutoring and provide personalized learning, to maximize users' learning quality (Boulay, 2019) and to address the social needs of students (Serholt et al, 2017). AI-based systems are characterized by their autonomy, adaptability and interactivity (Richards & Dignum, 2019;Xu, Wijekumar, Ramirez, Hu, & Irey, 2019). AI techniques can capture and analyze learners' behavioral and psychological data, connect to knowledge networks (Sullivan & Keith, 2019), change customized learning plans based on learners' responses, rather than being a set procedure designed by some experts.…”
Section: Introductionmentioning
confidence: 99%